Exploring Advances in Natural Plant Molecules for Allergic Rhinitis Immunomodulation in Vivo and in Vitro - Li B; Dong B; Xie L; Li Y (International Journal of General Medicine)
Bingquan Li,1,* Boyang Dong,1,* Liangzhen Xie,2 Yan Li2 1Graduate School, Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China; 2Ear-Nose-Throat Department, The First Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liangzhen Xie; Yan Li, Email xieliangzhen888111@163.com; liyan888111@163.comAbstract: Allergic rhinitis (AR) is a prevalent allergic disease that imposes significant economic burdens and life pressures on individuals, families, and society, particularly in the context of accelerating globalization and increasing pathogenic factors. Current clinical therapies for AR include antihistamines, glucocorticoids administered via various routes, leukotriene receptor antagonists, immunotherapy, and several decongestants. These treatments have demonstrated efficacy in alleviating clinical symptoms and pathological states. However, with the growing awareness of AR and rising expectations for improvements in quality of life, these treatments have become associated with a higher incidence of side effects and an elevated risk of drug resistance. Furthermore, the development of AR is intricately associated with dysregulation of the immune system, yet the underlying pathogenetic mechanisms remain incompletely understood. In contrast, widely available natural plant molecules offer multiple targeting pathways that uniquely modify the typical pathophysiology of AR through immunomodulatory processes. This review presents a comprehensive analysis of both in vivo and in vitro studies on natural plant molecules that modulate immunity for treating AR. Additionally, we examine their specific mechanisms of action in animal models to provide new insights for developing safe and effective targeted therapies while guiding experimental and clinical applications against AR. Keywords: natural plant molecules, allergic rhinitis, immunomodulation, therapeutic mechanism, research progress